2015
DOI: 10.4103/2229-516x.162282
|View full text |Cite
|
Sign up to set email alerts
|

Formative assessment in postgraduate medical education - Perceptions of students and teachers

Abstract: Context:One of the most important factors of medical education that can revolutionize the learning process in postgraduate students (PGs) is assessment for learning by means of formative assessment (FA). FA is directed at steering and fostering learning of the students by providing feedback to the learner. However, though theoretically well suited to postgraduate training, evidence are emerging that engaging stakeholders in FA in daily clinical practice is quite complex.Aims:To explore perceptions of PGs and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 17 publications
(16 reference statements)
2
24
0
1
Order By: Relevance
“…Page | 7 required in the education and training to achieve a reasonable and comprehensive assessment strategy (Juwah, C. et al 2004;Veloski, J. et al 2006;Celebi, N. et al 2009;Holmboe, J. et al 2010;Sharma, S. et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Page | 7 required in the education and training to achieve a reasonable and comprehensive assessment strategy (Juwah, C. et al 2004;Veloski, J. et al 2006;Celebi, N. et al 2009;Holmboe, J. et al 2010;Sharma, S. et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus although formative assessment, in theory, is highly suitable for postgraduate medical education, international empirical studies have shown that implementing formative assessment often proves unsuccessful or very difficult. [25][26][27][28] Since formative assessment takes place in the context of complex clinical practice, it is consequently important to understand how these dynamic processes unfold. 15 However, to the best of our knowledge, no studies focused on formative assessment in postgraduate medical education have made use of direct observation.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al, who found prevalence of cervical rib to be 1.22 %. 8 Prevalence rate on Americans was found to be 0.5-1 %. 9 Brewin et al 5 found a prevalence rate of 0.74% in a mixed sex and ethnicity population in London.…”
Section: Discussionmentioning
confidence: 98%